A review on association of vaginal microbiota with female reproductive tract health in childbearing women - Ling CHEN; Fen-hong KANG; Xue-yan LIN (Editorial Office of Chinese Journal of Public Health, 2022)
By maintaining a dynamic balance of mutual restriction and coordination between the host and environment, vaginal microflora plays important roles in the occurrence and development of reproductive tract diseases and in female reproductive health. In this study, we review progresses in researches on the relationship between vaginal microflora and reproductive tract health and related mechanisms in childbearing women for understanding the role of vaginal microflora in reproductive tract health of childbearing and improving clinical diagnosis and treatment of female reproductive tract diseases.